Control circuits in power electronics : practical issues in design and implementation - Castilla, Miguel (The Institution of Engineering and Technology, 2016)
Control circuits are a key element in the operation and performance of power electronics converters. This book describes practical issues related to the design and implementation of these control circuits, with a focus on the presentation of the state-of-the-art control solutions, including circuit technology, design techniques, and implementation issues. Topics covered include PWM-based sliding mode control schemes for DC-DC power converters; synthetic-ripple hysteretic controllers for DC/DC converters; one-cycle controlled single phase power inverters; digital PWM control of high-frequency DC-DC switched-mode power converters; microcontroller-based electronic ballasts for high-intensity-discharge lamps; FPGA-based controllers for direct sliding mode control of PWM boost rectifiers; DSP controllers for three-phase unity-power-factor rectifiers and voltage-sourced inverters; FPGADSP controllers for DC-DC converters in renewable energy applications; topologies, modulation and control of multilevel converters; state-of-the-art intelligent gate drivers for IGBT power modules; control of integrated switched capacitor power converters; DSP-based natural frame control schemes for three-phase unity-power-factor rectifiers; dual-core DSP for control and communication in AC microgrids; and the use of computational intelligence for designing power electronics converters. Control Circuits in Power Electronics is an essential reading for researchers, advanced students and practicing design engineers working in power electronics.
Keywords: Power electronics.; Electronic circuits.; elektronické knihy; electronic books